Panel data econometrics - Arellano, Manuel (Oxford ; New York : Oxford University Press, 2003)
Presenting some of the main topics in panel data econometrics, this work deals with static models, time series models with error components, and with dynamics and predeterminedness. The author concentrates on linear models, and emphasizes the roles of heterogeneity and dynamics in panel data modelling.
Includes bibliographical references (p. 215-226) and index.
oif 27/04/15; 05/05/15; nmn 27/05/15
Loans
Keywords: Econometrics; Panel analysis